2020
DOI: 10.1007/s00262-020-02748-9
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinase inhibition sensitizes melanoma cells to T-cell-mediated cytotoxicity

Abstract: Although immunotherapy has achieved impressive durable clinical responses, many cancers respond only temporarily or not at all to immunotherapy. To find novel, targetable mechanisms of resistance to immunotherapy, patient-derived melanoma cell lines were transduced with 576 open reading frames, or exposed to arrayed libraries of 850 bioactive compounds, prior to co-culture with autologous tumor-infiltrating lymphocytes (TILs). The synergy between the targets and TILs to induce apoptosis, and the mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…In contrast, CD4+ T cells secrete a variety of cytokines with direct effector functions and activate other immune cells such as B cells and CD8 T cells [38].In the present study, we also observed that AURKA inhibited the immune-infiltrating levels of anti-tumor immune cells (DC, B cells, CD4+ T cells, and CD8+ T cells) in the TME, while increasing the infiltration level of tumor immune escape-promoting cells (MDOS, ). Our findings are consistent with that of previous reports [31,39,40]suggesting that AURKA can inhibit the increased level of antitumor immune cell infiltration in the TME. We postulate that the formation of the immunosuppressive microenvironment is promoted for the following.…”
Section: Mutations In Genes In Normal Cells Promote the Progression O...supporting
confidence: 94%
See 1 more Smart Citation
“…In contrast, CD4+ T cells secrete a variety of cytokines with direct effector functions and activate other immune cells such as B cells and CD8 T cells [38].In the present study, we also observed that AURKA inhibited the immune-infiltrating levels of anti-tumor immune cells (DC, B cells, CD4+ T cells, and CD8+ T cells) in the TME, while increasing the infiltration level of tumor immune escape-promoting cells (MDOS, ). Our findings are consistent with that of previous reports [31,39,40]suggesting that AURKA can inhibit the increased level of antitumor immune cell infiltration in the TME. We postulate that the formation of the immunosuppressive microenvironment is promoted for the following.…”
Section: Mutations In Genes In Normal Cells Promote the Progression O...supporting
confidence: 94%
“…Recent studies have demonstrated that AURKA, which is highly expressed in SKCM, inhibits effector T cell-mediated cytotoxicity [31]. At the same time, the functional annotation results indicated that AURKA influences the TME, therefore, we further investigated the correlation between AURKA and TME.…”
Section: Aurka Reshapes the Tumor Immunosuppressive Microenvironmentmentioning
confidence: 92%
“…Many previous studies have found that the expression level and activity of these two kinases are upregulated in different tumors (56)(57)(58). Furthermore, Punt et al reported that the transcriptome and protein levels of Aurora kinase have significant negative correlations with immunocyte infiltration, the immunotherapeutic response and survival in patients with melanoma, and Aurora kinases were identified to be involved in the resistance of melanoma cells to T-cell-mediated cytotoxicity (59). In our study, AURKA and AURKB were significantly negatively correlated with mast cell infiltration and KITLG expression levels in the analysis of multiple databases.…”
Section: Discussionmentioning
confidence: 99%
“…This substantiates the anti-proliferative effect of CM-272 on MO4 cells. Notably, p21 upregulation has been shown to sensitize melanoma cells to T-cell cytotoxicity ( 56 ). Accordingly, we found improved recognition of CM-272-treated tumors by T cells in vitro.…”
Section: Discussionmentioning
confidence: 99%